Cardiac electrophysiology :from cell to bedside - Zipes Douglas P.; Jalife, José (Philadelphia Elsevier Sounders, 2014)
Puts the knowledge in this subspecialty at your fingertips, giving you a well-rounded, expert grasp of every cardiac electrophysiology issue that affects your patient management.
Keywords: Arrhythmia; Electrophysiology; Arrhythmias, Cardiac; Electrophysiologic Techniques, Cardiac; Heart